ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REALISASI PEMBIAYAAN MURABAHAH UNTUK USAHA MIKRO AGRIBISNIS SEKTOR PERDAGANGAN (STUDI KASUS: KBMT BIL BARKAH, BOGOR) - Mahliza, Febrina; Tinaprilla, Netti (Forum Agribisnis, 2012)
Micro business has significant contribution to GDP and employment. Micro business in agriculture has the highest contribution. The problem faced by micro business in agriculture is the difficulty to get financed by conventional bank. Shari Microfinance is one of the financing alternatives. Baitul Mal wat Tanwil Cooperative (KBMT) Bil Barkah is one of Shari microfinance provider via murabahah funding. The purpose of this research is to analyze customer characteristics affecting murabahah funding acquirement. The sampling method used was convenience sampling and total sample used was 40 people. The collected data was processed by multiple regressions. The results shows the significant factors are education, business experience, monthly revenue and collateral.